A Multienzyme Reaction-Mediated Electrochemical Biosensor for Sensitive Detection of Organophosphorus Pesticides - Chengzhen Ji; Xuemei Tang; Ruiming Wen; Chengdong Xu; Jing Wei; Bingjun Han; Long Wu (Biosensors, 2024)
Ethephon (ETH), a commonly employed growth regulator, poses potential health risks due to its residue in fruits and vegetables, leading to both acute and subchronic toxicity. However, the detection accuracy of ETH is compromised by the color effects of the samples during the detection process. In this work, a multienzyme reaction-mediated electrochemical biosensor (MRMEC) was developed for the sensitive, rapid, and color-interference-resistant determination of ETH. Nanozymes Fe3O4@Au–Pt and graphene nanocomplexes (GN–Au NPs) were prepared as catalysts and signal amplifiers for MRMEC. Acetylcholinesterase (AChE), acetylcholine (ACh), and choline oxidase (CHOx) form a cascade enzyme reaction to produce H2O2 in an electrolytic cell. Fe3O4@Au–Pt has excellent peroxidase-like activity and can catalyze the oxidation of 3,3′,5,5′-tetramethvlbenzidine (TMB) in the presence of H2O2, resulting in a decrease in the characteristic peak current of TMB. Based on the inhibitory effect of ETH on AChE, the differential pulse voltammetry (DPV) current signal of TMB was used to detect ETH, offering the limit of detection (LOD) of 2.01 nmol L−1. The MRMEC method effectively analyzed ETH levels in mangoes, showing satisfactory precision (coefficient of variations, 2.88–15.97%) and recovery rate (92.18–110.72%). This biosensor holds promise for detecting various organophosphorus pesticides in food samples.